2019
DOI: 10.1186/s12889-019-6626-3
|View full text |Cite
|
Sign up to set email alerts
|

Participation in a Swedish cervical cancer screening program among women with psychiatric diagnoses: a population-based cohort study

Abstract: BackgroundIn Sweden, organized screening programs have significantly reduced the incidence of cervical cancer. For cancers overall, however, women with psychiatric diagnoses have lower survival rates than other women. This study explores whether women with psychiatric diagnoses participate in cervical cancer screening programs to a lesser extent than women on average, and whether there are disparities between psychiatric diagnostic groups based on grades of severity.MethodsBetween 2000 and 2010, 65,292 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…As examples, organized national screening programs for breast, colorectal, and cervical cancers across Europe and the United Kingdom have generally yielded reductions in cancer-related mortality as in the US; nevertheless, implementation still is incomplete, and participation rates vary. [47][48][49] Nonetheless, during a pandemic, these organized, nationally supported programs still can systematically offer cancer screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As examples, organized national screening programs for breast, colorectal, and cervical cancers across Europe and the United Kingdom have generally yielded reductions in cancer-related mortality as in the US; nevertheless, implementation still is incomplete, and participation rates vary. [47][48][49] Nonetheless, during a pandemic, these organized, nationally supported programs still can systematically offer cancer screening.…”
Section: Resultsmentioning
confidence: 99%
“…At a time when resources (staff, equipment, and supplies) are devoted to fighting the COVID‐19 pandemic and preparing for potential further rebounds, coordinated public health policy and multilevel approaches to implementation are warranted to support continued cancer screening in health care settings. As examples, organized national screening programs for breast, colorectal, and cervical cancers across Europe and the United Kingdom have generally yielded reductions in cancer‐related mortality as in the US; nevertheless, implementation still is incomplete, and participation rates vary 47‐49 . Nonetheless, during a pandemic, these organized, nationally supported programs still can systematically offer cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of disability included in this review was psychosocial disability, accounting for 47% of all studies ( n = 15), assessed as a psychiatric or mental health diagnosis, a history of psychiatric prescription, or self-reported mental status [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. One third (31.3%, n = 10) of the studies included used disability in general or combining different types of disability into a category of having a disability or no disability.…”
Section: Resultsmentioning
confidence: 99%
“…However, a previous review has shown that there are lower cancer screening rates in people with mental illness 13. Among patients with mental illness, patients with schizophrenia have been suggested to have a particularly low cancer screening rate 14. Our previous study demonstrated that in Japan the colorectal cancer screening rate in people with schizophrenia was 24.1%, which is much lower than that of the general population at 40.7% 15.…”
Section: Introductionmentioning
confidence: 93%